Post-Pemphigus Acanthomata Presenting as an Isolated, Hyperkeratotic Plaque - Rachita Pandya; Yanjia Zhou; Mansee Desai; Nancy Anderson; Ashley Elsensohn (MDPI AG, 2023)
Post-pemphigus acanthomas have been rarely discussed in the literature. A prior case series identified 47 cases of pemphigus vulgaris and 5 cases of pemphigus foliaceus, out of which 13 developed acanthomata as a part of the healing process. Additionally, a case report by Ohashi et al. reported similar recalcitrant lesions on the trunk of a patient with pemphigus foliaceus being treated with prednisolone, IVIG, plasma exchange, and cyclosporine. Some view post-pemphigus acanthomas as variants of hypertrophic pemphigus vulgaris, being difficult to diagnose when they present as only single lesions, with a clinical differential of an inflamed seborrheic keratosis or squamous cell carcinoma. Here, we present a case of a 52-year-old female with a history of pemphigus vulgaris and four months of only topical therapy (fluocinonide 0.05%) who presented with a painful, hyperkeratotic plaque on the right mid-back that was found to be a post-pemphigus acanthoma.